Scientometric tools in strategising the development of scientific periodicals: the case of the journal Digital Models and Solutions - V.A. Blaginin; E.V. Sokolova (Цифровые модели и решения)
The present study is dedicated to the development of scientometric tools for the strategic advancement of a scientific periodical, exemplified by the journal of the Ural State University of Economics, “Digital Models and Solutions”. The research involved a compre hensive analysis of the publication activity and thematic profile of this journal, as well as a general statistical examination of Russian academic journals indexed in the Russian Science Citation Index (RSCI) that pertain to the upper echelon of the State Rubricator of Scientific and Technical Information category “Informatics”. Primary data collection was conducted using the platforms elibrary.ru, CyberLeninka and CrossRef. The data analysis and visuali zation were performed utilizing the R programming language. The construction of thematic networks was carried out using the VOSviewer software, while additional visualization of certain results was executed using Scimago Graphica. The findings of the study identify the current positioning of the journal “Digital Models and Solutions” among scientific publi cations in informatics, define target scientometric indicators for its prospective growth, and propose specific recommendations for the strategic development of the journal, aimed at enhancing its competitiveness and scholarly impact.